PERILAKU KUAT TEKAN MORTAR SEMEN PASANGAN DENGAN ABU SABUT CANGKANG SAWIT YANG DIOVEN DAN TIDAK DIOVEN - Elhusna Elhusna; Agustin Gunawan; Dofi Hendro Fogi (Universitas Bengkulu, 2019)
The order of mortar cement which used to bond individual units of masonry and to cover masonry wall keeps increasing. Meanwhile, the natural source of cement is limited. This article is the report of the research of the behaviour of mortar compression strength which used palm oil fibrous shell ash as the additive of cement. The ash used in this research was strained by strainer number 200. The ash discerned to the difference between the oven and unoven one. The proportions of cement and sand that used were 1:3 dan 1:5. The percentages of each of the ash were varied by the increment 2,5% between 0 to 10 %. 200 mortar 50 mm cubes distributed to each cell of samples were used according to ASTM C109/C109M-02. The concistency and the workability of the mortar was done by flow table test according to ASTM C-270. The mortar cubes were cured in water since the mall were gotten off. The compession test was held according to SNI 03-6825-2002 at 28 days of the cubes age. The results of analysis of variance (anova) of the mortar strength which used ovened ash were significant for the strength of the proportion 1:5 and unsignificant for the strength of 1:3 of the proportion. The strength of the significant one was inceased 0.66% at the mortar which used 10% ash. The results of the anova of the mortar strength with unovened ash were significant for the mortarproportion 1:3 and unsignificant for the strength of 1:5 mortar proportion. The strength of the significant one was 1,54% higher at mortar with 2,5% ash compared to the one without the ash.